The Relationship between Transitive and Intransitive Verbs in English Language - Teddy Fiktorius (Universitas Ahmad Dahlan, 2019)
In the current research, the researcher employs descriptive method (library research) to elaborate on the relationship and differentiation between the English language transitive and intransitive verbs. The first parts explore the theoretical framework of the relationship and differentiation equipped with various sentences samples. The next part discusses the implications for English language teachers in coping with some grammatical confusion. Finally, some solutions as well as recommendations are proposed.